Quasi-static crushing of eggbox, cube, and modified cube foldcore sandwich structures. (October 2015) - Fathers, R.K.; Gattas, J.M.; You, Z.
Abstract: This paper explores a range of kirigami-inspired folded core structures for use in sandwich panels. Focus has been on assessing the energy-absorption capabilities of the cores, specifically on benchmarking core performance against the widely studied Miura-ori folded core. Four core architectures were investigated. Two cores are based on cube and eggbox known tessellated kirigami patterns. Two cores, the cube-strip and the diamond strip, are developed from geometric modifications of the cube tessellation. The cube strip is generated by removing face portions of the cube pattern that contribute little to energy absorption, effectively making a cellular square tube configuration. The diamond strip introduced a pre-folded origami pattern into the core which has been shown in previous research to substantially increase square tube energy absorption. The performance of each core is assessed under quasi-static loading with experimental and numerical analyses. The non-optimised diamond strip cube strip core offered a 41% increase in average force compared to the best-performing curved-crease Miura-type foldcore previously reported and a 92% improvement over the standard Miura-type foldcore. Abstract : Graphical abstract: Abstract : Highlights: An investigation of energy-absorption of non-Miura folded sandwich cores. Experimental and numerical analyses of four core types are presented. Two core types are based on known cube and eggbox tessellated kirigami patterns. Two core types are based on geometric modifications of the cube core. A modified core has energy absorption 41% above the best previously reported foldcore.